Dangerous effects of toxic substances - M.Daliyev (Genius Journals, 2024)
Toxic substances are easily absorbed into all organs, including the brain, and can cause acute and chronic poisoning. Organic mercury compounds damage capillaries, causing dilation of blood vessels, increased permeability, and fluid transfer from blood to tissues, a process that exacerbates damage to the central nervous system. Compounds have a toxic effect on the heart, disrupt the regulation of heart activity. Toxic substances can accumulate in the body for a long time. A long latent period from the moment of contact with toxic substances to the appearance of clinical manifestations is characteristic of such substances. Severe poisonings are characterize
Keywords: poisoning; institutes; ,curriculum development